Desarrollo de la Consultora GBP - Buitrago Rodríguez, Felipe (2022)
Development of a consulting company focused on the replacement of single-use plastic. Within the document, the steps that were followed for the development of the consulting company, identified problem, client's profile, business model and the minimum viable product developed by the authors are presented. Likewise, there are the surveys carried out on potential clients and references used during the execution of the project.